Bronchoscopy and cricothyrotomy: results from cadavers embalmed with Thiel’s method compared to other embalming methods and living subjects: Bronhoskopija in krikotirotomija: primerjava Thielove fiksirne metode z ostalimi metodami fiksacije - Feigl, Georg; Benkhadra, Mehdi; Lenfant, François; Trouilloud, Pierre; Anderhuber, Friedrich; Bonniaud, Philippe; Fasel, Jean HD; Nemetz, Wolfgang (Acta Medico-Biotechnica, 2021)
Purpose: Cricothyrotomy and bronchoscopy were performed on cadavers embalmed according to Thiel’s method, and the results compared with findings from other types of cadavers and living subjects, to assess the suitability of such specimens for medical teaching and research.Methods: Blind cricothyrotomy was performed in 40 cadavers using two different devices (Cook and Portex sets) on each of 20 cadavers and the procedures were recorded by a monitoring fibreoptic bronchoscope placed in the larynx. Bronchoscopy was performed on another 22 cadavers. All procedures were videotaped and evaluated by board certified anatomists and anaesthetists. Tissue behaviour, ligament resistance, palpability of anatomical structures, mucosal colour and cadaver flexibility, especially during jaw thrust and tongue lift, were evaluated and qualitatively compared to conditions found in the living and to reports of studies using specimens embalmed with the classic formalin method. Where the procedures caused mucosal lesions, the damaged was assessed during subsequent dissection.Results: The cadavers were life-like in all criteria evaluated. Portex and Cook cricothyrotomy was feasible in all cases. Bronchoscopy was feasible in all cadavers without difficulty. Jaw thrust and tongue lift was never limited and lobar bronchi were always reached. Further advancement was limited in half of the cases by either the preservation liquid or the diameter of the segmental bronchi; in the remaining half, advancement into the smaller airways was limited only by their diameter.Conclusion: Cadavers fixed according to Thiel’s method are highly useable, life-like specimens for teaching and researching cricothyrotomy and bronchoscopy. The data obtained are transferable to the living, so research findings should be valid and teaching effective.
Keywords: Thiel’s method; coniotomy; bronchoscopy; embalming method; cricothyrotomy